2018
DOI: 10.24275/uam/izt/dcbs/hidro/2018v28n2/marchamalo
|View full text |Cite
|
Sign up to set email alerts
|

Responses of aquatic macroinvertebrates to human pressure in a tropical highland volcanic basin: Birrís River, Irazú Volcano (Costa Rica)

Abstract: Background. Tropical mountain rivers are strategic sources of water for human development while biological communities are indicators of the status of these ecosystems. However, volcanic basins close to large urban areas are affected by increasing human pressures that threaten the future of these ecosystems and their benefits to society. Goals. This paper analyzes the evolution of the responses of the aquatic macroinvertebrate assemblages in the face of increasing pressures in the Birrís River basin, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…As per their results, the increase in the sewage discharge into the western Gulf, a distinct change in the community structure was raised, and the Ostracoda and oligochaete classes were dominated in the area. Similarly, Marchamalo et al ( 2018 ) investigated the response of benthic invertebrates to human pressure in a volcanic basin at Birrís River. The results showed that the Chironomidae and Simuliidae families (Diptera order) and Baetidae family (Ephemeroptera order) predominated in the region throughout the year.…”
Section: Discussionmentioning
confidence: 99%
“…As per their results, the increase in the sewage discharge into the western Gulf, a distinct change in the community structure was raised, and the Ostracoda and oligochaete classes were dominated in the area. Similarly, Marchamalo et al ( 2018 ) investigated the response of benthic invertebrates to human pressure in a volcanic basin at Birrís River. The results showed that the Chironomidae and Simuliidae families (Diptera order) and Baetidae family (Ephemeroptera order) predominated in the region throughout the year.…”
Section: Discussionmentioning
confidence: 99%
“…While some authors provided specialized insight through examination of a particular taxonomic order (6.14%), suborder (one study on Amazonian damselflies; Brasil et al, 2017), or family (one study on dytiscid beetles in Finnish ponds, Liao et al, 2020), it was most common for studies to evaluate diversity metrics of the entire macroinvertebrate community (88.59%, Figure 1). Additional focal metrics often aimed to capture the degree of disturbance tolerance by highlighting specific taxa, such as the prevalence of Chironomidae or Oligochaeta (non-biting midge or aquatic worms, e.g., Marchamalo et al, 2018). Acknowledging the range of tolerance values within a single insect order, some studies specified the ratio of Hydropsychidae (a typically tolerant caddisfly family) to the rest of Trichoptera taxa in the benthic community (Rogers et al, 2002;Tszydel et al, 2015).…”
Section: Taxon-specific Metricsmentioning
confidence: 99%